DEPENDENCE OF VITAMIN CONTENT IN THE GEUM URBANUM AND GEUM RIVALE (GEUM, ROSACEAE) ORGANS ON THE RHYTHM OF SEASONAL DEVELOPMENT - T. V. Burchenko (Юг России: экология, развитие)
The aim of the research is to determine the optimal terms of the accumulation of vitamins by the organs of Geum depending on the rhythms of their seasonal development.Methods. The method for determining the vitamin C is based on the ability of ascorbic acid to change the color to blue in the acidic medium - 2,6 - dichlorophenolindophenol - to the leucoform, while ascorbic acid is oxidized to dehydroascorbic acid. Determination of vitamins A and E was carried out by reversed-phase high-performance liquid chromatography.Results. It was found that the highest indices of vitamin A and E in the leaves of G. urbanum and G. rivale are observed in July. In the rhizomes of avens, the maximum concentration of vitamins A and E is observed in March during their intensive growth, vitamin C in January. Decrease in the supply of rhizomes of plants with vitamins A and E continues in the autumn period, while for the vitamin C it is observed in the early spring. In the inflorescences, at the beginning of flowering, G. rivale L. and G. urbanum L. are characterized by the greatest content of vitamin A; by the end of flowering, vitamins E and C are accumulated more intensively.Conclusion. The leaves of wintering plants of G. urbanum L. and G. rivale L. continue to contain vitamins A, E, C despite low temperatures under snow cover and are not subject to significant destruction. During the winter rest period, the content of vitamin C in the roots reaches a maximum.